2009
DOI: 10.1007/s00192-009-0821-1
|View full text |Cite
|
Sign up to set email alerts
|

POP-Q, dynamic MR imaging, and perineal ultrasonography: do they agree in the quantification of female pelvic organ prolapse?

Abstract: Introduction and hypothesis This study evaluates the agreement in prolapse staging between clinical examination, dynamic magnetic resonance (MR), imaging and perineal ultrasonography. Methods Anatomical landmarks in the anterior, central, and posterior compartment were assessed in relation to three reference lines on dynamic MR imaging and one reference line on dynamic ultrasonography. These measurements were compared to the according POP-Q measurements. Agreement between the three methods was analyzed with Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 20 publications
1
43
0
4
Order By: Relevance
“…18 scans (11.4%) were not analysable (17 of poor quality in the POP group and 1 missing in the control group). The mean age was 49.5 years [standard deviation (SD), 14 Enterocoele on two-dimensional transperineal ultrasound measuring 12 mm below reference line (solid horizontal line refers to the reference line parallel to postero-inferior margin of symphysis pubis and arrow marked E measures the enterocoele perpendicular to the reference line). AC, anal canal; B, bladder; E, enterocoele; P, probe; R, rectum; SP, symphysis pubis; U, urethra.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…18 scans (11.4%) were not analysable (17 of poor quality in the POP group and 1 missing in the control group). The mean age was 49.5 years [standard deviation (SD), 14 Enterocoele on two-dimensional transperineal ultrasound measuring 12 mm below reference line (solid horizontal line refers to the reference line parallel to postero-inferior margin of symphysis pubis and arrow marked E measures the enterocoele perpendicular to the reference line). AC, anal canal; B, bladder; E, enterocoele; P, probe; R, rectum; SP, symphysis pubis; U, urethra.…”
Section: Resultsmentioning
confidence: 99%
“…The patients were scanned in the supine position and without using any rectal or vaginal contrast. 9,14 PFUS consisted of two-dimensional (2D) transperineal ultrasound (TPUS) and high-frequency 2D/three-dimensional (3D) endovaginal ultrasound (EVUS). TPUS was performed with the patient placed in the dorsal lithotomy, with the hips flexed and abducted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was independent of the staging method and reference lines used. 9 Study by Etlik O et al showed physical examination and MR findings were very concordant in the diagnosis of pelvic prolapse and statistical correlations in the stages of prolapse were established between both of the methods (P<0.01 for anterior and middle comportment, P<0.05 for posterior comportment. 10 Similar study by Deval et al showed intra-operative findings were considered the gold standard against which physical examination, dynamic colpocystodefecography and MRI were compared.…”
Section: Discussionmentioning
confidence: 95%